MULTI RING AND MULTI LEVEL BASKETBALL GAME DEVELOPMENT AS A LEARNING MEDIUM IN PHYSICAL, SPORTS, AND HEALTH EDUCATION IN ELEMENTARY SCHOOLS (Journal of Physical Education and Sports, 2012)
Basketball game is one of the big ball games which is aimed at enriching movement experiences and at improving students’ fitness. Not all schools in the implementation of Physical Education teaching teach basketball, among others due to the lack of supporting infrastructure, there is not any sports field or the school yard is not wide enough, many students experience difficulties in learning and practicing the game, and also teachers are less mastering the teaching of basketball techniques. Therefore, we need to develop basketball game modification model that is adjusted to elementary students’ age and the schools’ condition. Development procedures used consist of some levels: 1)analysing product to develop, 2) developing the initial product of basketball game model, 3) asking for experts’ validation, 4) trying out the fields in small-group test and big-group test, 5) revising the product and the result of developed product. Instruments used for identifying students’ physical intensity are 1) pulse-taking data before and after learning, 2) psychomotor, cognitive, affective response using questionnaire, 3) basketball basic techniques. The results of the research had been found: 1) multi ring and multi level basketball game model, 2) the effectiveness of the game model is able to improve students’ physical activity; we can see this by the pulse-rate improvement before and after joining the basketball learning lesson. The average of pulse-rate improvement after the treatment was as much as 82,3 % and pulse-rate maximum improvement was as much as 48,4 %, 3) this basketball game model is able to overcome the limited available infrastructure. This is based on the questionnaire-filling result, in the less category was 0 %, fairly good category was 9,3%, good category was 61,3 %, and very good category was as much as 29,3 %. Conclusions: the usage of basketball game model as a Physical Education lesson’s learning media for elementary school students gives impact physical intensity, and is able to overcome the lack of infrastructure problem at schools for basketball game model and also gives feeling of excitement for students to join the basketball game learning. Suggestion for Physical Education teachers in elementary school is they can use this model in teaching basketball game material at school.